Assessing nursing students' perceptions of hospital learning environment. - Chan, Dominic S. (Curtin University, 1999)
Nursing is essentially a practical discipline and as such, clinical practice plays an important part in the nursing curriculum. Clinical education is a vital component in the curricula of pre-registration nursing courses and provides student nurses with the opportunity to combine cognitive, psychomotor, and affective skills. Clinical field placement is an integral element in the overall pre-registration nursing program. Clinical practice enables the student to develop competencies in the application of knowledge, skills, and attitudes to clinical field situations. However, the time allocation for the clinical component of pre-registration nursing courses can be rather limited. It is, therefore, vital that the short but valuable clinical time be utilised effectively and productively.One of the objectives of this study was to develop and validate an instrument, the Clinical Learning Environment Inventory (CLEI), to assess nursing students' perceptions of hospital learning environment during clinical practice. Data were collected from 138 second year nursing students in a major university school of nursing in South Australia. Both quantitative and qualitative data were collected. The study confirmed the reliability and validity of the CLEI for use in the hospital learning environment.A second objective was to investigate associations of the CLEI with outcomes. Students' perceptions of the outcome of their clinical placement were found to be strongly associated with all five scales of the CLEI namely; Individualisation, Innovation, Involvement, Personalisation, and Task Orientation. The quantitative and qualitative findings reinforced each other. A third objective was to determine whether there were any differences in students' perceptions of the actual learning environment provided and that preferred by students. It was found that there were significant differences in students' perceptions of the actual clinical learning environment and their preferred clinical learning environment. Findings from the study suggested that students preferred a more positive and favourable clinical environment than they perceived as being actually present.